2022
DOI: 10.3389/fonc.2022.833582
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-138 Abates Fibroblast Motility With Effect on Invasion of Adjacent Cancer Cells

Abstract: BackgroundRecent studies have shown aberrant expression of micro-RNAs in cancer-associated fibroblasts (CAFs). This study aimed to investigate miR-138 dysregulation in CAFs in oral squamous cell carcinoma (OSCC) and its effects on their phenotype and invasion of adjacent OSCC cells.MethodsExpression of miR-138 was first investigated in OSCC lesions (n = 53) and OSCC-derived CAFs (n = 15). MiR-138 mimics and inhibitors were used to functionally investigate the role of miR-138 on CAF phenotype and the resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Nonetheless, research has confirmed that it is present in low levels in cervical cancer specimens, with close and positive correlations between its level and the degree of cervical intraepithelial lesions [13]. Thus, miR-138 level is intimately associated with the occurrence, development and extent of cervical neoplasm [13]. This study has shown significantly lower relative expression level of miR-138 in cervical cancer tissues than in nearby healthy tissues.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Nonetheless, research has confirmed that it is present in low levels in cervical cancer specimens, with close and positive correlations between its level and the degree of cervical intraepithelial lesions [13]. Thus, miR-138 level is intimately associated with the occurrence, development and extent of cervical neoplasm [13]. This study has shown significantly lower relative expression level of miR-138 in cervical cancer tissues than in nearby healthy tissues.…”
Section: Discussionsupporting
confidence: 59%
“…However, the actual function of miR-138 in development of cancer is not yet completely fully understood [12]. Nonetheless, research has confirmed that it is present in low levels in cervical cancer specimens, with close and positive correlations between its level and the degree of cervical intraepithelial lesions [13]. Thus, miR-138 level is intimately associated with the occurrence, development and extent of cervical neoplasm [13].…”
Section: Discussionmentioning
confidence: 99%